2010
DOI: 10.2174/187152810792231904
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nuclear Factor-κB in Inflammatory Lung Disease

Abstract: Nuclear factor-kappaB (NF-kappaB) is one of the most important transcription factors; it has a key role in inflammatory and immune responses, cell adhesion, developmental signals, and anti-apoptosis process. Inflammatory lung diseases such as asthma and chronic obstructive pulmonary disease (COPD) are major causes of morbidity and mortality worldwide. In this review, we highlight the role of NF-kappaB in inflammatory lung disease, the strategies which block the activation of NF-kappaB, and the therapeutic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…The eukaryotic transcription factor NF-κB regulates a wide variety of target genes that encode multiple inflammatory cytokines, such as TNF-α, IL-1β, IL-4, IL-5, IL-13, ICAM-1, and VCAM-1, all of which are closely implicated in the pathogenesis of asthma, as mentioned above [8]. Our results indicate that LE exerts anti-NF-κB actions in lung tissues of OVA-challenged mice.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The eukaryotic transcription factor NF-κB regulates a wide variety of target genes that encode multiple inflammatory cytokines, such as TNF-α, IL-1β, IL-4, IL-5, IL-13, ICAM-1, and VCAM-1, all of which are closely implicated in the pathogenesis of asthma, as mentioned above [8]. Our results indicate that LE exerts anti-NF-κB actions in lung tissues of OVA-challenged mice.…”
Section: Discussionsupporting
confidence: 67%
“…inducing the transcription of various proinflammatory mediators [8], we hypothesized that LE would attenuate airway inflammatory reactions by suppressing NF-κB activation. To address this issue, we first studied the nuclear translocation of the NF-κB p65 subunit in lung tissues after OVA challenge.…”
Section: Le Suppresses the Nuclear Translocation Of Nf-κ κB And Phospmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor-kappa B (NF-kB), which is the ubiquitous eukaryotic transcription factor that regulates gene expression of proinflammatory cytokines and enzymes, has a key role in inflammatory and immune responses, including asthma (3). Its increased activation has been demonstrated in the lungs after allergen challenge and in airway epithelial cells and macrophages of asthmatic patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it has been reported that FXR significantly decrease various cytokines involved in inflammation [38,39] and FXR ligand UDCA has been shown to inhibit these actions in OVA-sensitized mouse asthma model [17], thus our results confirm previous observations. Nuclear factor kappa B (NF-kB) is a pleotropic transcription factor that plays a central role in asthma and induces the recruitment of inflammatory cells and drive antigen-induced inflammation that is important contributor to adaptive immune response [40,41]. Activation of FXR has been shown to inhibit hepatic inflammation by antagonizing the NF-kB signalling and target gene expression in vivo [19].…”
Section: Discussionmentioning
confidence: 99%